Cd & mn co-doped SnTe-based thermoelectric material and preparation method thereof

CN116634846BActive Publication Date: 2026-10-23ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310650223.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2026-10-23
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

专利(专利 CN 112670400 一种多孔SnTe热电材料的制备方法)虽然利用引入的孔隙极大降低了SnTe的热导率,但有可能会对材料的力学性能造成损害

Benefits of technology

1、本发明采用高温淬火、退火及快速热压烧结的样品制备工艺,制得一系列具有优异性能的Sn1.03-3xCdxMn2xTe块体热电材料。与液相法相比,本样品制备工艺流程简单、便于重复合成、稳定性高等优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116634846B_ABST
    Figure CN116634846B_ABST
Patent Text Reader

Abstract

The application discloses a kind of Cd&Mn co-doped SnTe-based thermoelectric materials and preparation method thereof, belong to energy conversion technical field.According to Sn 1.03‑3x Cd x Mn 2x Te (0≤x≤0.05) stoichiometric ratio Sn, Te, Cd, Mn powder is weighed, mixed uniformly in agate mortar, again using high temperature quenching, annealing sample preparation process, obtains Sn 1.03‑3x Cd x Mn 2x Te ingot material.Use agate mortar to grind ingot material to powder, powder is loaded into graphite mould, under certain temperature and pressure, quickly hot-press sample, obtain Sn 1.03‑3x Cd x Mn 2x Te bulk thermoelectric material.The thermoelectric material prepared by the application greatly reduces the thermal conductivity of SnTe, and significantly improves the Seebeck coefficient, thereby greatly enhancing the thermoelectric performance of SnTe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy conversion technology, specifically relating to a Cd&Mn co-doped SnTe-based thermoelectric material and its preparation method. Background Technology

[0002] Thermoelectric materials enable the conversion between thermal and electrical energy, offering significant applications in addressing waste heat emissions from industry and automobiles. The conversion efficiency of different forms of energy in the actual conversion process is determined by the material's thermoelectric figure of merit (ZT), which can be expressed as S. 2 σT / κ, where σ, S, κ, and T represent electrical conductivity, Seebeck coefficient, thermal conductivity, and absolute temperature, respectively. Generally, the conversion efficiency of thermoelectric materials is positively correlated with the ZT value, which means that high σ, S, and low κ are key to obtaining excellent thermoelectric materials.

[0003] Group IV-VI compounds are a class of thermoelectric materials used in the mid-temperature range, mainly including PbTe, GeTe, and SnTe. In waste heat recovery and conversion, SnTe and its alloys have gradually become a research focus due to their low price and environmental friendliness. However, due to SnTe's intrinsic high cation vacancies, high thermal conductivity, and large energy separation value, its original properties do not have a significant advantage. While the patent (patent CN 112670400, a method for preparing porous SnTe thermoelectric materials) greatly reduces the thermal conductivity of SnTe by introducing pores, it may potentially damage the material's mechanical properties. Jamwal et al.'s strategy of Ag and Cu co-doping only slightly optimized the Seebeck coefficient of the material, to the point that Sn... 1.03 The ZT value of Te only increased slightly (J. Alloys Compd., 2023, 954(5), 170182).

[0004] This application employs a bandgap convergence effect and carrier concentration optimization control strategy, using high-temperature quenching and annealing sample preparation processes, combined with rapid hot pressing, and utilizing the synergistic effect of multiple effects introduced by Cd & Mn co-doping. This results in a significant increase in the Seebeck coefficient and a decrease in thermal conductivity of SnTe, greatly enhancing the thermoelectric properties of SnTe. 0.91 Cd 0.04 Mn 0.08 The ZT value of the Te sample at 823 K was 1.25, which was 122% higher than that of the pure sample. Summary of the Invention

[0005] To address the aforementioned needs, the present invention aims to provide a Cd&Mn co-doped SnTe-based thermoelectric material and its preparation method. This method employs a solid-state synthesis approach, which is simple, reproducible, and easy for large-scale synthesis. The SnTe-based thermoelectric material prepared by this invention exhibits a high Seebeck coefficient and low thermal conductivity across the entire temperature range (298 K~823 K), resulting in a significant improvement in the thermoelectric performance of the doped sample.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: A Cd&Mn co-doped SnTe-based thermoelectric material with the general chemical formula Sn 1.03-3x Cd x Mn 2x Te (0≤x≤0.05). Preferably, the Cd&Mn co-doped SnTe-based thermoelectric material is specifically Sn. 1.03 Te、SnCd 0.01 Mn 0.02 Te、Sn 0.97 Cd 0.02 Mn 0.04 Te、Sn 0.94 Cd 0.03 Mn 0.06 Te、Sn 0.91 Cd 0.04 Mn 0.08 Te、Sn 0.88 Cd 0.05 Mn 0.1 Te.

[0007] Furthermore, the aforementioned Cd&Mn co-doped SnTe-based thermoelectric material uses Sn, Te, Cd, and Mn powders as raw reactants. These are weighed according to the required stoichiometric ratio, mixed evenly in an agate mortar, and then prepared using a sample preparation process involving high-temperature quenching and annealing. This is followed by rapid hot-pressing sintering to produce Sn with high density and pure phase. 1.03-3x Cd x Mn 2x Te bulk thermoelectric material. The specific steps of the preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 1.03-3x Cd x Mn 2xWeigh Sn, Te, Cd, and Mn powders according to the stoichiometric ratio of Te (0≤x≤0.05), mix them thoroughly in an agate mortar, and then place the mixture into an alumina crucible, which is then placed in a quartz tube. Vacuum is applied and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level of the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature to 900–1100 °C after 5–9 h, hold for 3–7 h, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 500–800 °C for 30–60 h, followed by another quench in cold water.

[0008] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed for 15-30 min at 40-70 MPa and 500-600 ℃ to obtain high-density Sn. 1.03-3x Cd x Mn 2x Te bulk thermoelectric materials.

[0009] Based on the above technical solution, the beneficial effects of the present invention are as follows: 1. This invention employs a sample preparation process involving high-temperature quenching, annealing, and rapid hot-pressing sintering to obtain a series of Sn samples with excellent properties. 1.03-3x Cd x Mn 2x Te bulk thermoelectric materials. Compared with the liquid phase method, the preparation process of this sample is simple, easy to repeat, and has high stability.

[0010] 2. The Sn prepared by this invention 1.03-3x Cd x Mn 2x Te bulk thermoelectric materials have a single phase and high density. For example Figure 1 As shown: Figure 1 Sn obtained by this invention 1.03-3x Cd x Mn 2x XRD patterns of Te (x=0, 0.01, 0.02, 0.03, 0.04, 0.05) thermoelectric materials. The phase of all samples is SnTe, and there are no other impurity phases. Figure 2 It is Sn 0.91 Cd 0.04 Mn 0.08 The SEM image of the fresh fracture surface of the Te bulk thermoelectric material shows that the prepared bulk sample has no obvious pores and has high density.

[0011] 3. The Sn prepared by this invention 1.03-3xCd x Mn 2x In SnTe thermoelectric materials, Sn self-compensation reduces the number of generated Sn vacancies, and Cd & Mn co-doping causes a convergence effect in the valence band of SnTe, leading to a significant increase in the Seebeck coefficient. Furthermore, elemental doping reduces electrical conductivity, thereby greatly reducing the thermal conductivity of SnTe and ultimately significantly enhancing its thermoelectric figure of merit. The Sn... 1.03- 3x Cd x Mn 2x The physical parameters of Te thermoelectric materials are as follows: Figures 3-6 As shown. Figure 3 This is a graph showing the change in thermal conductivity of the thermoelectric material with temperature. Figure 4 This is a graph showing the change in electrical conductivity of the thermoelectric material with temperature. Figure 5 This is a graph showing the Seebeck coefficient of the thermoelectric material as a function of temperature. Figure 6 This is a graph showing the thermoelectric figure of merit of the aforementioned thermoelectric material as a function of temperature. From... Figure 3 It can be seen that the lowest thermal conductivity of the thermoelectric material is 1.43 W / m K, compared to undoped Sn. 1.03 Te decreased by 53%; from Figure 5 It can be seen that the highest Seebeck coefficient of the thermoelectric material is 254 μV / K, which is significantly higher than that of undoped Cd & Mn Sn. 1.03 Te, increased by 78%; from Figure 6 It can be seen that the highest thermoelectric figure of merit of the thermoelectric material is 1.25, compared to the undoped Sn in the control example. 1.03 Te increased by 122%. Attached Figure Description

[0012] Figure 1 For Sn 1.03-3x Cd x Mn 2x X-ray diffraction (XRD) patterns of samples with values ​​of Te (x=0, 0.01, 0.02, 0.03, 0.04, 0.05). Figure 2 For Sn 0.91 Cd 0.04 Mn 0.08 Scanning electron microscope (SEM) image of the fresh fracture surface of the Te bulk sample. Figure 3 Thermal conductivity (κ) diagrams for control examples, examples 1, 2, 3, 4, and 5. Figure 4 The conductivity (σ) graphs for Comparative Examples and Examples 1, 2, 3, 4, and 5 are shown. Figure 5 Seebeck coefficient (S) plots for control examples, examples 1, 2, 3, 4, and 5. Figure 6 Thermoelectric figure of merit (ZT) diagrams for Comparative Examples, Examples 1, 2, 3, 4, and 5. Detailed Implementation

[0013] To further understand the present invention, the following detailed description of the embodiments and accompanying drawings is provided in conjunction with the examples and drawings, but these should not be construed as limiting the scope of protection of the present invention.

[0014] Sn with x=0 1.03-3x Cd x Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 1.03 Weigh 2.445g of Sn powder and 2.552g of Te powder according to their stoichiometric ratio, mix them thoroughly in an agate mortar, and then place the mixture into an alumina crucible, which is then placed in a quartz tube. Vacuum is applied and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level of the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature to 1000 °C after 7 hours, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650 °C for 48 hours, followed by a second quench in cold water.

[0015] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550 ℃ for 25 min using a rapid hot pressing process to obtain high-density Sn. 1.03 Te bulk thermoelectric materials.

[0016] Characterization showed that the Sn prepared in this embodiment... 1.03 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity ranges from 7.21 W / m K to 3.06 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 The conductivity is 702383 S / m~100000 S / m (see attached diagram). Figure 4 The Seebeck coefficient is 25 μV / K to 143 μV / K (see attached). Figure 5 The final ZT value was 0.017–0.56 (see attached). Figure 6 ).

[0017] Example 1: High-density SnCd 0.01 Mn 0.02 Preparation of Te bulk thermoelectric materials Sn with x=0.01 1.03-3x Cd x Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on SnCd 0.01 Mn 0.02 Weigh out 2.374g of Sn powder, 2.552g of Te powder, 0.023g of Cd powder, and 0.022g of Mn powder according to their stoichiometric ratio. Mix them thoroughly in an agate mortar. The mixture is then placed in an alumina crucible, which is subsequently placed inside a quartz tube. A vacuum is applied, and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level of the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature for 7 hours to 1000 °C, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650 °C for 48 hours, followed by another cold water quench.

[0018] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550 ℃ for 25 min using a rapid hot pressing process to obtain high-density SnCd. 0.01 Mn 0.02 Te bulk thermoelectric materials.

[0019] Characterization showed that the SnCd prepared in this embodiment... 0.01 Mn 0.02 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity is 5.50 W / m K to 2.18 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 The conductivity is 486000 S / m~61700 S / m (see attached diagram). Figure 4 The Seebeck coefficient is 31 μV / K to 182 μV / K (see attached). Figure 5 The final ZT value was 0.025–0.77 (see attached). Figure 6 Compared with the control example, the thermal conductivity of the sample decreased by 29%; the Seebeck coefficient of the sample increased by 27%; and the ZT value of the final sample was enhanced by 38%.

[0020] Example 2: High-density Sn 0.97 Cd 0.02 Mn 0.04 Preparation of Te bulk thermoelectric materials Sn with x=0.02 1.03-3x Cdx Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 0.97 Cd 0.02 Mn 0.04 Weigh out 2.303g of Sn powder, 2.552g of Te powder, 0.045g of Cd powder, and 0.044g of Mn powder according to their stoichiometric ratio. Mix them thoroughly in an agate mortar. The mixture is then placed in an alumina crucible, which is subsequently placed inside a quartz tube. A vacuum is applied, and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level of the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature for 7 hours to 1000 °C, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650 °C for 48 hours, followed by another cold water quench.

[0021] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550 ℃ for 25 min using a rapid hot pressing process to obtain high-density Sn. 0.97 Cd 0.02 Mn 0.04 Te bulk thermoelectric materials.

[0022] Characterization showed that the Sn prepared in this embodiment... 0.97 Cd 0.02 Mn 0.04 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity is 3.64 W / m K to 1.80 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 ); conductivity is 251000 S / m~44800 S / m (attached) Figure 4 The Seebeck coefficient is 53 μV / K to 219 μV / K (see attached). Figure 5 The final ZT value was 0.058–0.98 (see attached). Figure 6 Compared with the control example, the thermal conductivity of the sample decreased by 41%; the Seebeck coefficient of the sample increased by 53%; and the ZT value of the final sample was enhanced by 75%.

[0023] Example 3: High-density Sn 0.94 Cd 0.03 Mn 0.06 Preparation of Te bulk thermoelectric materials Sn with x=0.031.03-3x Cd x Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 0.94 Cd 0.03 Mn 0.06 Weigh out 2.232g of Sn powder, 2.552g of Te powder, 0.067g of Cd powder, and 0.066g of Mn powder according to their stoichiometric ratio. Mix them thoroughly in an agate mortar. The mixture is then placed in an alumina crucible, which is subsequently placed inside a quartz tube. A vacuum is applied, and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level in the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature for 7 hours to 1000℃, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650℃ for 48 hours, followed by another cold water quench.

[0024] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550℃ for 25 min using a rapid hot pressing process to obtain high-density Sn. 0.94 Cd 0.03 Mn 0.06 Te bulk thermoelectric materials.

[0025] Characterization showed that the Sn prepared in this embodiment... 0.94 Cd 0.03 Mn 0.06 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity is 2.84 W / m K to 1.52 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 ); conductivity is 181000 S / m~37300 S / m (attached) Figure 4 The Seebeck coefficient is 69 μV / K to 236 μV / K (see attached). Figure 5 The final ZT value was 0.09–1.12 (see appendix). Figure 6 Compared with the control example, the thermal conductivity of the sample in this embodiment decreased significantly by 50%; the Seebeck coefficient of the sample increased significantly by 65%; and the ZT value of the final sample was greatly enhanced by 100%.

[0026] Example 4: High-density Sn 0.91 Cd 0.04 Mn 0.08 Preparation of Te bulk thermoelectric materials Sn with x=0.04 1.03-3x Cd x Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 0.91 Cd 0.04 Mn 0.08 Weigh out 2.161g of Sn powder, 2.552g of Te powder, 0.090g of Cd powder, and 0.089g of Mn powder according to their stoichiometric ratio. Mix them thoroughly in an agate mortar. The mixture is then placed in an alumina crucible, which is subsequently placed inside a quartz tube. A vacuum is applied, and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level of the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature for 7 hours to 1000℃, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650℃ for 48 hours, followed by another cold water quench.

[0027] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550℃ for 25 min using a rapid hot pressing process to obtain high-density Sn. 0.91 Cd 0.04 Mn 0.08 Te bulk thermoelectric materials.

[0028] Characterization showed that the Sn prepared in this embodiment... 0.91 Cd 0.04 Mn 0.08 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity is 2.74 W / m K to 1.44 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 ); conductivity is 123000 S / m~33200 S / m (attached) Figure 4 The Seebeck coefficient is 78 μV / K to 254 μV / K (see attached). Figure 5 The final ZT value was 0.08–1.25 (see attached). Figure 6 Compared with the control example, the thermal conductivity of the sample in this embodiment decreased significantly by 53%; the Seebeck coefficient of the sample increased significantly by 78%; and the ZT value of the final sample was greatly enhanced by 122%.

[0029] Example 5: High-density Sn 0.88 Cd 0.05 Mn 0.1 Preparation of Te bulk thermoelectric materials Sn with x=0.05 1.03-3x Cd x Mn 2x The specific steps of the Te thermoelectric material preparation method are as follows: (1) High-temperature quenching and annealing process: based on Sn 0.88 Cd 0.05 Mn 0.1 Weigh out 2.089g of Sn powder, 2.552g of Te powder, 0.112g of Cd powder, and 0.110g of Mn powder according to their stoichiometric ratio. Mix them thoroughly in an agate mortar. The mixture is then placed in an alumina crucible, which is subsequently placed inside a quartz tube. A vacuum is applied, and the tube is sealed at high temperature. The quartz tube used has a diameter of 15 mm and a wall thickness of 1.5 mm. During the vacuum process, the vacuum level in the quartz tube is maintained below 1 Pa. The quartz tube is then placed in a quenching furnace for a high-temperature solid-state reaction. The temperature program is as follows: heat from room temperature for 7 hours to 1000 °C, hold for 5 hours, and then quench in cold water. After quenching, the quartz tube containing the sample is placed in a muffle furnace and annealed at 650 °C for 48 hours, followed by another cold water quench.

[0030] (2) Rapid hot pressing process: The ingot sample obtained in (1) is manually ground into powder in an agate mortar, then placed into a graphite mold, and vacuum hot pressed at 50 MPa and 550 ℃ for 25 min using a rapid hot pressing process to obtain high-density Sn. 0.88 Cd 0.05 Mn 0.1 Te bulk thermoelectric materials.

[0031] Characterization showed that the Sn prepared in this embodiment... 0.88 Cd 0.05 Mn 0.1 The phase of the Te thermoelectric material is SnTe (see attached) Figure 1 The thermal conductivity is 3.07 W / m K to 1.43 W / m K in the range of 298 K to 823 K (see attached diagram). Figure 3 ); conductivity is 168000 S / m~33300 S / m (attached) Figure 4 The Seebeck coefficient is 65 μV / K to 245 μV / K (see attached). Figure 5 The final ZT value was 0.07–1.15 (see attached). Figure 6 Compared with the control example, the thermal conductivity of the sample in this embodiment decreased significantly by 53%; the Seebeck coefficient of the sample increased significantly by 71%; and the ZT value of the final sample was greatly enhanced by 105%.

[0032] In summary, the prepared Sn 1.03-3x Cd x Mn 2xTe thermoelectric materials, among which the sample with doping amount x=0.04 has the best performance, Sn 0.91 Cd 0.04 Mn 0.08 The Te samples exhibited thermal conductivity ranging from 2.74 W / m K to 1.44 W / m K and electrical conductivity ranging from 123,000 S / m to 33,200 S / m in the range of 298 K to 823 K, Seebeck coefficient ranging from 78 μV / K to 254 μV / K, and final ZT values ​​ranging from 0.08 to 1.25.

Claims

1. A Cd&Mn co-doped SnTe-based thermoelectric material, characterized in that, The thermoelectric material is prepared by a method comprising the following steps: (1) High-temperature quenching and annealing process: based on Sn 1.03-3x Cd x Mn 2x Weigh Sn, Te, Cd, and Mn powders according to their stoichiometric ratio (x=0.04), mix them thoroughly in an agate mortar, place the mixed powder into an alumina crucible, then place it into a quartz tube, evacuate and seal the tube at high temperature; place the quartz tube into a quenching furnace for a high-temperature solid-state reaction, the temperature program is as follows: heat to 900-1100℃ after 5-9 hours at room temperature, hold for 3-7 hours, then quench in cold water; place the quenched quartz tube containing the sample into a muffle furnace and anneal at 500-800℃ for 30-60 hours, then quench in cold water again; (2) Rapid hot pressing process: The ingot sample obtained in step (1) is manually ground into powder in an agate mortar, then placed into a graphite mold and vacuum hot pressed at 40~70 MPa and 500~600℃ for 15~30 min to obtain high-density Sn. 0.91 Cd 0.04 Mn 0.08 Te bulk thermoelectric materials.

2. The Cd&Mn co-doped SnTe-based thermoelectric material according to claim 1, characterized in that, The thermoelectric material has the chemical formula Sn. 0.91 Cd 0.04 Mn 0.08 Te, whose ZT value is 0.08 to 1.25 in the temperature range of 298 K to 823 K.